Prevention of breast cancer brain metastases by minocycline-loaded liposomes - Vaz, Prevention of breast cancer brain metastases by minocycline-loaded liposomes (2022)
Tese de mestrado, Ciências Biofarmacêuticas, 2022, Universidade de Lisboa, Faculdade de Farmácia